61.1k views
3 votes
3(s-5)/4 -3 = 4s- (s-3)/2
pls answer fast​

User Hughesjmh
by
4.4k points

1 Answer

6 votes

Answer:


s = (9± √( - 39) )/(4)

Explanation:


(3(s - 5))/(4 - 3) = (4s * (s - 3))/(2)

➡️
(3(s - 5))/(1) = 2s * (s - 3)

➡️
3s - 15 = 2 {s}^(2) - 6s

➡️
3s - 15 - 2 {s}^(2) + 6s = 0

➡️
9s - 15 - 2 {s}^(2) = 0

➡️
- 2 {s}^(2) + 9s - 15 = 0

➡️
2 {s}^(2) - 9s + 15 = 0

➡️
s = \frac{ - ( - 9)± \sqrt{( - 9 {)}^(2) - 4 * 2 * 15} }{2 * 2}

➡️
s = (9± √(81 - 120) )/(4)

➡️
s = (9± √( - 39) )/(4)

➡️
s∉ℝ

User Slayer
by
4.7k points